TUBA1A mutation can cause a hydranencephaly-like severe form of cortical dysgenesis - Yokoi, Setsuri (Sci Rep, 2015)
TUBA1A mutations cause a wide spectrum of lissencephaly and brain malformations. Here, we report two patients with severe cortical dysgeneses, one with an extremely thin cerebral parenchyma apparently looking like hydranencephaly and the other with lissencephaly accompanied by marked hydrocephalus, both harbouring novel de novo missense mutations of TUBA1A. To elucidate how the various TUBA1A mutations affect the severity of the phenotype, we examined the capacity of the mutant protein to incorporate into the endogenous microtubule network in transfected COS7 cells by measuring line density using line extraction in an immunofluorescence study. The mutants responsible for severe phenotypes were found to incorporate extensively into the network. To determine how each mutant alters the microtubule stability, we examined cold-induced microtubule depolymerisation in fibroblasts. The depolymerisation of patients’ fibroblasts occurred earlier than that of control fibroblasts, suggesting that microtubules bearing mutated tubulins are unstable. Both mutations are predicted to participate in lateral interactions of microtubules. Our data suggest that the TUBA1A mutations disrupting lateral interactions have pronounced dominant-negative effects on microtubule dynamics that are associated with the severe end of the lissencephaly spectrum.